A new approach to mutagenesis in Clostridium acetobutylicum - Furness, Lindsey (2017)
Clostridium acetobutylicum has long been of interest to industry due to its solventogenic capabilities through an endogenous acetone-butanol-ethanol (ABE) fermentation pathway. Cooksley et al.,(2012) carried out a large scale targeted mutagenesis experiment of genes in the C. acetobutylicum ATCC 824 ABE pathway. In this study they were unable to knock out several genes central to the pathway, including the main hydrogenase hydA and thiolase thl ; in the case of a third genephosphotransbutyrylase ptb, a knock out mutant was isolated only where a frameshift mutation in the thiolase gene had also occurred. The aim of this study was to use a modified ClosTron with a negative selection marker to: 1) create gene knock down strains of hydA, thl and ptb respectively in C.acetobutylicum ATCC 824 ; 2) cure these of the ClosTron plasmid to create pure knock out mutant strains using a toxic negative selection marker codA (cytosine deaminase) ; 3) analyse resultant mutant strains produced for potentially "compensatory” mutations, such was the case in Cooksley et al., (2012) where a double knock-out strain of ptb and thl was isolated, despite not achieving single knock-outs of either gene individually. If possible, the phenotypes of these mutants would be analysed using GC-MS fermentation analysis. This study was successful in isolating a ClosTron plasmid cured thl knock out mutant, but was unable to carry out wide scale analysis in the timescale available. However, this mutant does serve as proof of the method, using a modified ClosTron, and enables future research into isolation of mutants previously impossible to achieve.